2017
DOI: 10.1002/adhm.201700368
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Exposure of Bioactive Growth Factor in 3D Amyloid Hydrogel for Stem Cells Differentiation

Abstract: promoting regeneration. [3] Hydrogels present a unique microstructure to the encapsulated cells influencing cell signaling and hence cellular fate. Peptide hydrogels are a class of physical hydrogels where the component peptides self-assemble noncovalently to form an ordered nanostructure [4] and eventually supramolecular networks, which entrap water for gelation. [5] Recently with the advent of protein engineering, relatively simple peptide based hydrogels have gained increasing attention in biomaterial dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 73 publications
2
37
0
Order By: Relevance
“…The rheological data including stress-strain rheology measurement showed that all these hydrogels are soft and thixotropic (Supplementary Fig. 3c and d) as shown previously for many amyloid hydrogels 16,[21][22][23][24]31 . The FTIR data of dried hydrogel fibrils showed cross-β-sheet rich structure ( Supplementary Fig.…”
Section: Design and Characterization Of Amyloid Hydrogels For Developsupporting
confidence: 81%
See 1 more Smart Citation
“…The rheological data including stress-strain rheology measurement showed that all these hydrogels are soft and thixotropic (Supplementary Fig. 3c and d) as shown previously for many amyloid hydrogels 16,[21][22][23][24]31 . The FTIR data of dried hydrogel fibrils showed cross-β-sheet rich structure ( Supplementary Fig.…”
Section: Design and Characterization Of Amyloid Hydrogels For Developsupporting
confidence: 81%
“…Amyloids also exhibit native functions in host organisms such as matrix formation in melanosome biogenesis 17 and storage of hormones in secretory granules 18 . Irrespective of primary sequence, amyloid fibrils of many proteins/peptides also showed robust cell adhesion and hydrogels composed of amyloid fibrils can promote stem cell differentiation to neurons 16,[19][20][21][22][23][24] . Many advantages that distinguish amyloid hydrogels from other peptides/protein-based hydrogels, include i) cross-β structure of amyloid network possessing a unique combination of hydrophobic and hydrophilic surfaces, with an ability to bind to various small molecules and biomolecules with a high affinity [25][26][27][28] ii) they are highly stable and resistant to extreme conditions, such as pH, temperature and proteases 29,30 .…”
Section: Amyloids Are Originally Implicated As Cytotoxic Protein Matementioning
confidence: 99%
“…Increased secretion of Alb might have contributed to the aggregation of PLGA architectures due to the viscous and glial properties of Alb. [26] Similarly, the levels of MRP were also augmented, which participates in the regulation of redistributing intracellular constituents to protect the cells. [26] It is believed that the adherence of individual architectures and aggregation of multicellularladen PLGA PMs could to a good extent represent the vascularized tumor microtissues in vitro.…”
Section: Formation Of Tumor Microtissues and Bioefficacy Assessmentsmentioning
confidence: 99%
“…7,8 With the support of natural or synthetic polymers which were safety and stability, 3D innovative culture systems were developed to enhance the adhesion, proliferation and increase the release of secreted factors by cultured cells. [9][10][11] Hydrogels are a 3D network made of natural or synthetic polymers crosslinked that can entrap large volume of water or biological fluid. [12][13][14] In recent years, hydrogels have been employed to generate three-dimensional (3D) models that better mimic the specific native microenvironment compared to 2D cell cultures.…”
Section: Introductionmentioning
confidence: 99%